A Path from Traditional Bullying to Cyberbullying in South Korea: Examining the Roles of Self-Control and Deviant Peer Association in the Different Forms of Bullying - Kim, Jihoon (Journal of interpersonal violence, 2022)
Despite a recent growth in studies on cyberbullying, extant knowledge on the underlying mechanisms of cyberbullying remain limited. The objective of the present study is to explore the dynamics of cyberbullying via traditional bullying, self-control, and delinquent peer association. Specifically, the following hypotheses guide the present study: (1) traditional bullying, low self-control, and delinquent peer association are predictive of cyberbullying, respectively, (2) the interaction between traditional bullying and low self-control has a significant impact on cyberbullying, and (3) the interaction between traditional bullying and delinquent peer association has a significant impact on cyberbullying. The present study relies on five waves of the Korean Youth Panel Survey (KYPS), a representative sample of South Korean adolescents. Data collection occurred annually and respondents were 14 years old at the first wave in 2003. KYPS is an almost gender-equal and racially/ethnically homogenous sample. Results of cross-lagged dynamic panel models show (1) significant effects of traditional bullying on cyberbullying with and without low self-control and delinquent peer affiliation, (2) the respective roles of self-control and delinquent peer association in the prediction of cyberbullying, and (3) an interaction effect between low self-control and traditional bullying on cyberbullying. These findings demonstrate the theoretical validity of self-control theory and social learning theory in online delinquent behavior as well as confirm their cross-cultural generalizability in a non-Western sample. The findings also highlight the importance of investing in early life-course prevention/intervention programs and policies to prevent and/or reduce the occurrence of bullying, regardless of whether it is being perpetrated face-to-face or online, and these programs and policies should also target components to improve self-control and reduce delinquent peer associations.